Veículo transportador de remédio - SANTOS, Alisson Gabriel Gonçalves dos; MARTIN, Ana Carolina de Souza Martinez; NASCIMENTO, Arthur Santana; VENTURA, Erick Angelo dos Santos; MORAES, Gabriel Fellipe de; FELIX, João Marcelo; FERRAZ, Jonatas Silva (186, 2022)
Com a Revolução Industrial, o conceito de moderno de tecnologia foi se desenvolvendo e com esses avanços técnicas de mecânicas mais complexas e a introdução a eletricidade foram começando a ser usadas, o que permitiu alimentar máquinas com pequenos motores compactos. Os robôs fazem parte de uma tecnologia que vem de longa data, mas que nos ultimos anos vem alimentando fabricas, sociedades e sonhos de engenheiros e os aficionados por tecnologias. Os primeiros robôs modernos eram utilizados em fábricas industriais, máquinas fixas que eram capazes de realizar tarefas e diminuir a necessidade de força humana. Leonardo Da Vinci criou um autômato baseado em uma armadura de um cavalheiro, ele poderia mover seus braços e pescoço e até abrir sua boca. O trabalho aqui apresentado tem como meta desenvolver um protótipo de carrinho autônomo que tem a capacidade de levar componentes médicos a setores de um hospital. A ideia é não utilizar profissionais para fazer esse tipo de serviço, utilizando esses profissionais em outras funções mais apropriada dentro do hospital. Nos escritos a seguir, são mensurados o tipo de veículo que pode fazer esse tipo de serviço, os componentes que o grupo utilizou para o projeto. O projeto em si usa um veículo movido a bateria, controlado por microcontrolador Arduino Uno, sensor de comunicação via bluetooth e controle por APP no celular. Por questões práticas, a programação para um veículo dentro do hospital pode ser orientado para rodar em cada andar do hospital. Já para o projeto aqui mostrado, o controle será feito via bluetooth pelo celular.

With the Industrial Revolution, the concept of modern technology developed, and with these technical advances in more complex mechanics and the introduction of electricity, machines began to be powered by small, compact motors. Robots are part of a long-standing technology that, in recent years, has fueled factories, societies, and the dreams of engineers and technology enthusiasts. The first modern robots were used in industrial factories; they were fixed machines capable of performing tasks and reducing the need for human labor. Leonardo Da Vinci created an automaton based on a knight's armor; it could move its arms and neck and even open its mouth. The work presented here aims to develop a prototype of an autonomous cart capable of transporting medical components to different areas of a hospital. The idea is to avoid using professionals for this type of service, utilizing them in other more appropriate functions within the hospital. The following text describes the type of vehicle that can perform this service and the components used by the group for the project. The project itself uses a battery-powered vehicle, controlled by an Arduino Uno microcontroller, a Bluetooth communication sensor, and control via a mobile app. For practical reasons, the programming for a vehicle within the hospital can be oriented to run on each floor of the hospital. For the project shown here, however, control will be done via Bluetooth on the mobile phone. With the Industrial Revolution, the concept of modern technology developed, and with these advances, more complex mechanical techniques and the introduction of electricity began to be used, which allowed machines to be powered by small, compact motors. Robots are part of a technology that has been around for a long time, but in recent years has been fueling factories, societies, and the dreams of engineers and technology enthusiasts. The first modern robots were used in industrial factories, fixed machines that were able to perform tasks and reduce the need for human strength. Leonardo Da Vinci created an automaton based on a knight's armor; it could move its arms and neck and even open its mouth. The work presented here aims to develop a prototype of an autonomous cart capable of transporting medical components to different areas of a hospital. The idea is to avoid using professionals for this type of service, utilizing them in other more appropriate functions within the hospital. The following text describes the type of vehicle that can perform this service and the components used by the group for the project. The project itself uses a battery-powered vehicle controlled by an Arduino Uno microcontroller, a Bluetooth communication sensor, and control via a mobile app. For practical reasons, the programming for a vehicle within the hospital can be oriented to operate on each floor. However, for the project shown here, control will be via Bluetooth using a mobile phone.
medicine transport vehicle
Keywords: Veículos automotores (protótipo); Veículos autônomos; Microcontrolador; Assistência hospitalar; Controle e Processos Industriais